Penerapan Metode Simple Additive Pada Sistem Pendukung Keputusan Untuk Pemilihan Handphone - Salamun, Salamun; Sukri, Sukri; Permadi, Kelvin (CV. Information Technology Training Center - Indonesia (ITTC), 2024)
The choice of mobile phone is an important decision in today's information technology era. In this context, the application of the Simple Additive method in the decision support system (DSS) becomes relevant to assist users in choosing a mobile phone that suits their needs and preferences. The Simple Additive method provides a simple yet effective framework for combining diverse criteria for evaluating mobile options. This study aims to develop SPK based on the Simple Additive method to improve accuracy and efficiency in the decision-making process of mobile phone selection. Through data analysis and system testing, it is hoped that the results of this research can make a positive contribution to the development of decision support systems for mobile phone selection. The purpose of this study is to implement an Android-based decision support system to assist users in choosing a mobile phone that suits their needs. Data collection is in the form of interviews and literature studies. This Mobile Selection Decision Support System was built with the help of Simple Additive Weighting in choosing mobile phones based on user needs and MySQL as a data storage. This Decision Support System for Mobile Selection was tested using black box testing successfully and system validation got results that were in accordance with the brand and specifications of the Mobile Phone. This Mobile Selection Decision Support System is expected to make it easier for users to choose the mobile phone needed.